2023
DOI: 10.3390/healthcare11040465
|View full text |Cite
|
Sign up to set email alerts
|

The Health-Seeking Behavior of the Elderly with Non-Communicable Diseases in Coastal Areas of Vietnam

Abstract: This study aimed to analyze the utilization of health care facilities and the health-seeking behavior of elderly people with non-communicable diseases and find the factors that affect them. A cross-sectional study was conducted in seven coastal areas of the Thua Thien Hue province, Vietnam, using a sample of 370 elderly people aged over 60 years. Chi-square and multiple logistic regression analyses were used to examine the factors associated with the utilization of health care services. The participants’ avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The study has also found that majority (64%) sought and utilized healthcare from established health institutions like hospitals. These ndings are similar to a study by [24] on 'the healthseeking behavior of the elderly with non-communicable diseases in coastal areas of Vietnam', which showed that 69.8% of the total participants exhibited health-seeking behaviors. [6] also found that the elderlies had a positive behavior towards seeking help in regards to the health care.…”
Section: Discussionsupporting
confidence: 88%
“…The study has also found that majority (64%) sought and utilized healthcare from established health institutions like hospitals. These ndings are similar to a study by [24] on 'the healthseeking behavior of the elderly with non-communicable diseases in coastal areas of Vietnam', which showed that 69.8% of the total participants exhibited health-seeking behaviors. [6] also found that the elderlies had a positive behavior towards seeking help in regards to the health care.…”
Section: Discussionsupporting
confidence: 88%
“…From ten articles included, eight [15][16][17][18]20,[22][23][24] were community-based cross-sectional studies while two 19,21 were health facility-based cross-sectional studies. The total study participants recruited in the study was 63,498 adults with NCDs.…”
Section: Characteristics Of Study Included In the Review And Meta-ana...mentioning
confidence: 99%
“…Among these are older age > 60, 15,17 having hypertension OR urban residency, 15 being female gender, 17 Educational status high school and above, 17,23 getting support during treatment, being hospitalized in the past, alcohol consumption, 20 being government employed, perceived as having good health status, 22 presence of NCD in the family members, knowledge of NCD risks, having more than one NCD, presence of health insurance, needing health care counseling, and economic class being middle and upper. 24…”
Section: Factors Associated With Health-seeking Behavior For Non-comm...mentioning
confidence: 99%
“…Popular criteria that can be chosen for evaluation include the level of physical and mental satisfaction with social relationships and the living environment 8 . The number of people living below the poverty line is higher in Vietnam’s coastal areas than in other regions, and national health standards are either unmet or below the national average 9 . Moreover, residents living in these areas usually have to endure various problems, such as access to hygienic water and transportation difficulties 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The number of people living below the poverty line is higher in Vietnam’s coastal areas than in other regions, and national health standards are either unmet or below the national average 9 . Moreover, residents living in these areas usually have to endure various problems, such as access to hygienic water and transportation difficulties 9 . Despite the difficulties and challenges in the QoL of people living along coastlines, there is a lack of reported investigations on this topic in Vietnam, despite the country having one of the longest coastlines in Asia 10 .…”
Section: Introductionmentioning
confidence: 99%